A longitudinal study of voluntary disclosure quality in the annual reports of innovative firms. Issue 1 (2nd May 2017) - Lim, Si Jie; White, Gregory; Lee, Alina; Yuningsih, Yuni
Abstract : Purpose: This paper aims to measure mean voluntary intellectual capital disclosure (ICD) quality score for a sample of Australian Stock Exchange-listed biotechnology firms in the 2003, 2006 and 2010 reporting periods. The aim was to use data for the same companies over the whole period to discover whether the quality of voluntary reporting practice was improving over time, measuring lagged-mean ICD quality score against possible determinants of management disclosure practice. Design/methodology/approach: Mean ICD quality score, and associated frequency data, was measured against possible determinants of managers' disclosure practice. The dependent variable was an 18-item classification of ICD based on Sveiby's Intangible Assets Monitor (Sveiby, 1997 ). Data collected from S&P Capital IQ database were used to compare ICD disclosure quality with possible drivers: competition (capital intensity); performance (profit and market returns); monitoring (audit firm and ownership); and control variables (revenue and leverage). Findings: Mean voluntary disclosures of internal capital and external capital lower the quality over time using paired sample t -test comparison against 2003 as a base year. The lowest quality disclosure was about human capital, and the highest quality was about internal capital. Individual disclosure items within internal, external and human capital classification showed that internal capital items (intellectual property, corporate culture, management processes and financial relations) and external capital item (customers) were the significant contributors. Investigation of drivers using Spearman's correlation against lagged ICD data showed that performance (relative market returns) and monitoring (ownership diffusion) were significant drivers of voluntary ICD, both in expected and unexpected ways. Originality/value: Voluntary ICD quality and quantity are rarely measured in the same paper. The findings are unique and interesting especially for innovative Australian R&D firms when compared to recent findings for a larger sample of French companies.